PENGARUH KOMPETENSI KEPALA DESA TERHADAP KEBERHASILAN PEMBANGUNAN DESA DI DESA RANOLAMBOT KECAMATAN KAWANGKOAN BARAT KABUPATEN MINAHASA - ONSU, CHAKLIN VANESA; TULUSAN, FEMMY; MAMBO, RULLY (Sam Ratulangi University, 2018)
This study aims to determine and analyze the magnitude of the leader of Village Head Competenceto the Success of Village Development in Ranolambot Village.The method that writer use in this research is quantitative method, is research method based onphilosophy of positivism, used for researcher on population or sample . The sampling technique used is asimple random sampling technique from research in Ranolambot Village of 55 people. Data analysistechniques used are simple linear regression analysis and simple correlation analysisBased on the analysis of Correlation Coefficient (r) = 0.812 while the coefficient of determination(rÂ²) = 0.659. The result shows that the coefficient of determination is 65,9%. With these results can beexplained that the increase of Village Development Success in by Village Head Competency of 65.9% while34.1% is determined by other factors. Based on the results of the above research, the hypothesis put forwardcan be accepted that there is a degree of linkage and determination of power between the Village Head'sCompetence to the Successful Village Development in Ranolambot Village.Based on the results of significant tests obtained Fcount = 102.542 at a significant level of 0.05with degrees of freedom (df) = n - 2 = 53, then Ftabel 4.02. From the dat it is obtained that Fcount is greaterthan Ftable where Fcount 102.542> 4.02. Then Ha accepted and H0 rejected. This proves that there is asignificant amount of influence between the Village Head's Competence on the Success of VillageDevelopment in Ranolambot Village.Keywords: Village Head Competency, Successful Village Development